2017
DOI: 10.1088/1361-648x/aa5377
|View full text |Cite
|
Sign up to set email alerts
|

Gate-controlled valley transport and Goos–Hänchen effect in monolayer WS2

Abstract: Based on a Dirac-like Hamiltonian and coherent scattering formalism, we study the spin-valley transport and Goos-Hänchen-like (GHL) effect of transmitted and reflected electrons in a gated monolayer WS. Our results show that the lateral shift of spin-polarized electrons is strongly dependent on the width of the gated region and can be positive or negative in both Klein tunneling and classical motion regimes. The absolute values of the lateral displacements at resonance positions can be considerably enhanced wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Similar results have also been reported in the GHL shift of electron beam transmitted through a ferromagnetic silicene [44]. Moreover, in our recent work [40], GHL shift of both transmitted and reflected electrons in a gated monolayer WS 2 was studied. Interestingly, it was shown that in contrast to the transmitted beam, the GHL shift of reflected electrons is not invariant under simultaneous interchange of spin and valley indexes.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar results have also been reported in the GHL shift of electron beam transmitted through a ferromagnetic silicene [44]. Moreover, in our recent work [40], GHL shift of both transmitted and reflected electrons in a gated monolayer WS 2 was studied. Interestingly, it was shown that in contrast to the transmitted beam, the GHL shift of reflected electrons is not invariant under simultaneous interchange of spin and valley indexes.…”
Section: Introductionsupporting
confidence: 85%
“…In the vicinity of resonance positions the lateral shift can be greatly enhanced (see Refs. [32,40]). At resonance positions which are determined by the condition k 2x d = nπ, (n = 1, 2, 3, ....), the heterojunction becomes transparent (T = 1) and σ τ tr,sz acquires local maxima which are obtained from σ τ tr,sz k2xd=nπ =…”
Section: B T and Ghl Shift In Type-b Heterojunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we can see in Fig. 8(a)-(b) perfect transmissions for normally incident electrons (θ = 0), regardless of the potential strengths and the number of ripples in y direction, which is a typical signature of Klein tunneling [30,33]. Moreover, the transmis- sion profile is symmetrical about (θ = 0) due to the absence of an external magnetic field along x direction [23].…”
Section: Resultsmentioning
confidence: 81%
“…The reflected P-polarized light is collected and analyzed by the photodetector and the angle of incidence is θ. The SF11 glass is adopted as the prism because of its high refractive index [44]. The Au thin film coated BK7 glass slide is attached to the base of an equilateral prism made of high refractive index glass through index matching fluid [45].…”
Section: Theoretical Model and Methodsmentioning
confidence: 99%